2017
DOI: 10.15698/mic2017.04.566
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus type I signal peptidase: essential or not essential, that’s the question

Abstract: Secretion of proteins into the extracellular environment is crucial for the normal physiology and virulence of pathogenic bacteria. Type I signal peptidase (SPase I) mediates the final step of bacterial secretion, by cleaving proteins at their signal peptide once they are translocated by the Sec or twin-arginine (Tat) translocon. SPase I has long been thought to be essential for viability in multiple bacterial pathogens. Challenging this view, we and others have recently created Staphylococcus aureus bacteria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The Lgt enzyme contributes to virulence of S. pneumoniae [21] and S. aureus [51] in mouse infection models. The Lsp enzyme is required for the full virulence of L. monocytogenes [60], Mycobacterium tuberculosis [13] and S. aureus [61]. In the current study, and using a mouse model of systemic infection, it was shown that the Lgt and Lsp enzymes influence the virulence of the highly virulent S. suis serotype 2 ST7 strain SC84.…”
Section: Discussionmentioning
confidence: 56%
“…The Lgt enzyme contributes to virulence of S. pneumoniae [21] and S. aureus [51] in mouse infection models. The Lsp enzyme is required for the full virulence of L. monocytogenes [60], Mycobacterium tuberculosis [13] and S. aureus [61]. In the current study, and using a mouse model of systemic infection, it was shown that the Lgt and Lsp enzymes influence the virulence of the highly virulent S. suis serotype 2 ST7 strain SC84.…”
Section: Discussionmentioning
confidence: 56%
“…The gene agrD encodes a precursor peptide consisting of a core peptide that is flanked by an N-terminal amphipathic helical region and a C-terminal highly negatively charged recognition sequence [Thoendel and Horswill, 2009]. AgrD is processed by AgrB, a membrane protein with endopeptidase activity, and an additional protease that is thought to be SpsB, the general signal peptidase associated with Sec and Tat secretion system [Hazenbos et al, 2017), via the following (proposed) pathway [Thoendel and Horswill, 2009]: Upon translation, the precursor peptide localizes to the inner leaflet of the cell membrane via the N-terminal amphipathic helix structure [Zhang et al, 2004]. In the next step, AgrB removes the C-terminal recognition sequence of the precursor peptide, which is followed by formation of the thiolactone ring between a Cys of the core peptide and its C-terminus [Thoendel and Horswill, 2009].…”
Section: Thiopeptidesmentioning
confidence: 99%
“…■ ARYLOMYCINS: NEW GRAM-NEGATIVE ANTIBIOTICS THAT TARGET LepB Arylomycin antibiotics are macrocyclic lipopeptides that inhibit bacterial type I signal peptidase (SPase), 63,64 an essential membrane-bound protease that cleaves signal sequences from preproteins following their translocation across the cytoplasmic membrane utilizing a serine-lysine dyad 65,66 (e.g., arylomycin A-C 16 12, Figure 4). There is considerable interest in advancing arylomycin antibiotics and related analogues for therapeutic applications.…”
mentioning
confidence: 99%